Śivakeśādipādāntastutiḥ of Śrī Śankara Bhagavatpādāchārya : with the commentary of Śrī Rāmakrishna Sūri - Śaṅkarācārya (Srirangam Sri Sankaragurukula series ;, 1943)
Hymn to Śiva, Hindu deity, by an exponent of the Advaita school in Hindu philosophy.